Impaired JNK signaling cooperates with Kras(G12D) expression to accelerate pancreatic ductal adenocarcinoma - Davies, Clare C. (2014)
The c-Jun N-terminal protein kinase (JNK) and its two direct activators, namely the mitogen-activated protein kinase (MAPK) kinase 4 (MKK4) and MKK7, constitute a signaling node frequently mutated in human pancreatic ductal adenocarcinoma (PDAC). Here we demonstrate the cooperative interaction of endogenous expression of Kras(G12D) with loss-of-function mutations in mkk4 or both, mkk4 and mkk7 genes in the pancreas. More specifically, impaired JNK signaling in a subpopulation of Pdx1-expressing cells dramatically accelerated the appearance of Kras(G12D)-induced acinar-to-ductal metaplasia and pancreatic intraepithelial neoplasias, which rapidly progressed to invasive PDAC within 10 weeks of age. Furthermore, inactivation of mkk4/mkk7 compromised acinar regeneration following acute inflammatory stress by locking damaged exocrine cells in a permanently de-differentiated state. Therefore, we propose that JNK signaling exerts its tumor suppressive function in the pancreas by antagonising the metaplastic conversion of acinar cells towards a ductal fate capable of responding to oncogenic stimulation.